WTO decision-making for the future - Patrick Low (World Trade Organization (WTO), 2011)
Decision making in the WTO has become ever more difficult as the number of members increases and the range of issues tackled broadens. This paper looks at reasons why aspects of decision-making might be changed and discusses a number of potential pitfalls that change would have to avoid, such as a dilution of commitments and fragmentation of the multilateral trading system. It then takes a detailed look at the notion of critical mass decision-making. It argues for this approach under certain conditions, as it would: i) allow for the emergence of a more progressive and responsive WTO agenda; ii) blunt the diversion of trade cooperation initiatives to RTAs; iii) allow more efficient differentiation in the levels of rights and obligations among a community of highly diverse economies; and iv) promote greater efficiency in multilaterally-based negotiations on trade rules, and perhaps, sectoral market access agreements.
Keywords: F1; F5; 330; GATT/WTO; negotiations; decision-making; Internationale Wirtschaftsorganisation; Verhandlungen; Entscheidung